2013
DOI: 10.1109/jsac.2013.131210
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and Security of Heterogeneous Distributed Storage Systems

Abstract: We study the capacity of heterogeneous distributed storage systems under repair dynamics. Examples of these systems include peer-to-peer storage clouds, wireless, and Internet caching systems. Nodes in a heterogeneous system can have different storage capacities and different repair bandwidths. We give lower and upper bounds on the system capacity. These bounds depend on either the average resources per node, or on a detailed knowledge of the node characteristics. Moreover, we study the case in which nodes may… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…13, we illustrate the overall picture for the case of n t = 1, n r = 2, and K = 10. While we do not yet have a lower bound or a tight DMT result, we believe that Scheme 3 is indeed likely to be superior 10 to all other schemes presented in this paper, namely the TDMA scheme, Schemes 1 and 2.…”
Section: Dmt Analysis For Schemementioning
confidence: 75%
See 2 more Smart Citations
“…13, we illustrate the overall picture for the case of n t = 1, n r = 2, and K = 10. While we do not yet have a lower bound or a tight DMT result, we believe that Scheme 3 is indeed likely to be superior 10 to all other schemes presented in this paper, namely the TDMA scheme, Schemes 1 and 2.…”
Section: Dmt Analysis For Schemementioning
confidence: 75%
“…[8,9]. for details), and codes lying on the storage-repair bandwidth tradeoff curve [8,10] are called regenerating codes. Explicit, tradeoff achieving regenerating codes can be found in the literature, see [9,11], among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent to the initial presentation of our codes in [1], there have been several other works on information theoretic security in distributed storage systems with repair considerations ( [48], [60]- [63]). In [48], the authors consider security from passive eavesdroppers and present outer bounds for the MSR setting that are tighter than those proposed in [33].…”
Section: A Codes For Distributed Storagementioning
confidence: 99%
“…For these parameters, it is shown that MBR is the one and only regime for which the resource requirements in the system do not increase when, in addition to security from an eavesdropper being able to read data stored in nodes, security from an eavesdropper who can also tap on to the data downloaded during repair is desired. Security in distributed storage systems with heterogeneous storage nodes is considered in [63].…”
Section: A Codes For Distributed Storagementioning
confidence: 99%